Ozone profile retrieval from limb scatter measurements in the HARTLEY bands: methodology, algorithm description, sensitivity studies, and validation - Rohen, G J; Savigny, Cv; Kaiser, J W; Llewellyn, E J; Froidevaux, L; Lopez-Puertas, M; Steck, T; Palm, M; Winkler, H; Burrows, J P; Sinnhuber, M; Bovensmann, H (Atmospheric chemistry and physics discussions, 2007)
SCIAMACHY limb scatter spectra have been used to retrieve atmospheric ozone profiles in the upper stratosphere and lower mesosphere. Through a selection of the wavelengths in the HARTLEY bands of ozone, profiles extending to 60 or 70 km altitude were retrieved. This constitutes the highest possible ozone profile information retrieval using the backscatter technique. Comparisons with profiles measured by a ground based radiometer in Norway, MIPAS on board ENVISAT, HALOE on UARS and MLS on AURA indicate a good agreement of the ozone profiles in the upper stratosphere within 10% but also an increasing overestimation above 50 to 55 km. Sensitivity studies show that solar zenith uncertainty and tangent height errors are the largest error sources. Although the tangent height is corrected through an own retrieval the correction seemed to be be worser with increasing altitude and remains therefore as the largest error source for this presented profile retrieval.